Getting to Grips with Autoinjectors: An Exploration of Handling Behaviors, Ease of Use, and Comfort of Autoinjector Users with Obesity - Larsen, Fie Falck; Mayorga, Ania; Nilsson, Niels Christian (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
Autoinjectors facilitate subcutaneous and intramuscular self-administration of medication, potentially reducing user errors, accidents, and anxiety related to needle phobia. While 2-step autoinjectors streamline the injection process, users exhibit varied handling behaviors, such as grip type, body posture, and skin handling, which can influence the force exerted and perceived ease of use and comfort. Understanding these behaviors can inform the design of devices and user communication materials to ensure safe and effective use. This study explored handling behaviors and user experiences with a modified 2-step autoinjector among 150 adults living with obesity (119 females and 31 males, 109 injection-experienced and 41 injection-inexperienced). Each participant performed six simulated injections into their skin using an autoinjector prefilled with water and without a needle. Tasks varied in injection site, skin handling, and body posture. Participants were allowed to familiarize themselves with the autoinjector and Instructions for Use (IFU) without specific guidance on skin handling or body posture. During the first task (abdominal injection with optional skin handling and body posture), a large proportion of participants did not adopt the grip type illustrated in the IFU (i.e., precision grip), with close to half using alternative grips. Most participants injected without skin handling, although a larger proportion of injection-experienced users employed skin folds. By comparing the tasks involving specific skin handling and body postures, it was found that abdominal injections were perceived as easier and more comfortable than seated injections. Thigh injections were rated as easier and more comfortable than abdominal and upper arm injections. The findings indicate that autoinjector designs should accommodate various grip types and physical capabilities to ensure effective use by all user groups. User communication materials should address grip types and skin handling techniques to optimize user experience and minimize risks. Recommendations for alternative injection sites and skin handling strategies may improve comfort and ease of use for users living with obesity.